The Effectiveness of Nutritional Screening in Hospital and Primary Care Settings: a Systematic Review - A Rashidian; V Mazarello Paes; S Murray; J Browne; R Southon; C Sharpin (Tehran University of Medical Sciences, 2005)
Objectives: To determine the effectiveness of nutritional screening programmes in improving quality of care and patient outcomes compared with usual care. Methods: Searches were performed on MEDLINE, EMBASE, CINHAL, the Cochrane database, and Current Controlled Trials. Due to the assumed scarcity of high quality evidence, interventional studies in hospital or primary care settings with adequate reporting and comparisons were considered as eligible. Team members met after reviewing the papers. Decisions on inclusion or exclusion of papers were made when all agreed. Two reviewers independently extracted data from included studies. Results: 705 abstracts were considered and thirty full-text papers were ordered and reviewed. Following further review of the extracted data two papers met the inclusion criteria. One was a clustered randomized study of 26 general practices to evaluate the effectiveness of screening for elderly ailments including malnutrition. It concluded nutritional screening did not improve referral to dieticians, detection of nutritional problems, or patients' quality of life. This study was underpowered for evaluating the effectiveness of nutritional screening. A non-randomized controlled before-after study of four hospital wards concluded that intervention improved weight recording, but not referral to dieticians or care at the mealtime of at risk patients. Discussion: Very few studies assess the effectiveness of nutritional screening with relevant outcomes and acceptable quality. The available evidence does not support systematic application of screening tools to hospital, or general practice patients. Given the current level of interest and political support for nutritional screening, further studies are urgently required.